A SAM framework for general equilibrium modeling and economic policy analysis - Truong Hong Trinh; Nguyen Manh Toan (Cogent Economics & Finance, 2020)
Social accounting matrix (SAM) is the linkage bridge between economic data and policy analysis in the general equilibrium models. While the empirical SAM is built upon economic data from the system of national accounts, the theoretical SAM is built upon the relation between economic actors in the economy. This paper proposes the SAM framework for the data linkage between the empirical SAM and the theoretical SAM, in which the SAM structure is defined with endogenous and exogenous blocks. The endogenous activities involve the production, income generation, and expenditures in the economy. The exogenous activities involve income redistribution, asset transfer, and capital accumulation of the economy. From the SAM framework, the general equilibrium model with the objective function of GDP, the equilibrium price system, and the constraints of macro balances are developed for experimental simulation and economic policy analysis. The paper contributes to the SAM framework that provides fundamental insights into economic data, SAM structure, and general equilibrium model for economic policy analysis.
Keywords: 330; economic data; GDP; general equilibrium; policy analysis; SAM